Fine mapping of qhir8 affecting in vivo haploid induction in maize - Chenxu Liu; Wei Li; Yu Zhong; Xin Dong; Haixiao Hu; Xiaolong Tian; Lele Wang; Baojian Chen; Chen Chen; Albrecht E. Melchinger; Shaojiang Chen (Theoretical and Applied Genetics, 2015)

Changes in the abundance and structure of bacterial communities under long-term fertilization treatments in a peanut monocropping system - Wuxing Liu; Qingling Wang; Baozhan Wang; Xiaobing Wang; Ashley E. Franks; Ying Teng; Zhengao Li; Yongming Luo (Plant and Soil, 2015)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Extreme variation of sulfur isotopic compositions in pyrite from the Qiuling sediment-hosted gold deposit, West Qinling orogen, central China: an in situ SIMS study with implications for the source of sulfur - Lei Chen; Xian-hua Li; Jian-wei Li; Albert H. Hofstra; Yu Liu; Alan E. Koenig (Mineralium Deposita, 2015)

Near infrared radiation protects against oxygen-glucose deprivation-induced neurotoxicity by down-regulating neuronal nitric oxide synthase (nNOS) activity in vitro - Zhanyang Yu; Zhaoyu Li; Ning Liu; Yunneng Jizhang; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Erratum to: Use of a whole-cell bioreporter, Acinetobacter baylyi, to estimate the genotoxicity and bioavailability of chromium(VI)-contaminated soils - Bo Jiang; Di Zhu; Yizhi Song; Dayi Zhang; Zengjun Liu; Xu Zhang; Wei E. Huang; Guanghe Li (Biotechnology Letters, 2015)

Heterologous biosynthesis of costunolide in Escherichia coli and yield improvement - Hua Yin; Yi-bin Zhuang; E-e Li; Hui-ping Bi; Wei Zhou; Tao Liu (Biotechnology Letters, 2015)

Near infrared radiation rescues mitochondrial dysfunction in cortical neurons after oxygen-glucose deprivation - Zhanyang Yu; Ning Liu; Jianhua Zhao; Yadan Li; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester - Chengcheng Liu; Yingli Zhou; Li Wang; Lei Han; Jin’e Lei; Hafiz Muhammad Ishaq; Jiru Xu (Current Microbiology, 2015)

How inhibiting nitrification affects nitrogen cycle and reduces environmental impacts of anthropogenic nitrogen input - Chunlian Qiao; Lingli Liu; Shuijin Hu; Jana E. Compton; Tara L. Greaver; Quanlin Li (Global Change Biology, 2015)
Anthropogenic activities, and in particular the use of synthetic nitrogen (N) fertilizer, have doubled global annual reactive N inputs in the past 50–100 years, causing deleterious effects on the environment through increased N leaching and nitrous oxide (N 2 O) and ammonia ( NH 3 ) emissions. Leaching and gaseous losses of N are greatly controlled by the net rate of microbial nitrification. Extensive experiments have been conducted to develop ways to inhibit this process through use of nitrification inhibitors ( NI ) in combination with fertilizers. Yet, no study has comprehensively assessed how inhibiting nitrification affects both hydrologic and gaseous losses of N and plant nitrogen use efficiency. We synthesized the results of 62 NI field studies and evaluated how NI application altered N cycle and ecosystem services in N‐enriched systems. Our results showed that inhibiting nitrification by NI application increased NH 3 emission (mean: 20%, 95% confidential interval: 33–67%), but reduced dissolved inorganic N leaching (−48%, −56% to −38%), N 2 O emission (−44%, −48% to −39%) and NO emission (−24%, −38% to −8%). This amounted to a net reduction of 16.5% in the total N release to the environment. Inhibiting nitrification also increased plant N recovery (58%, 34–93%) and productivity of grain (9%, 6–13%), straw (15%, 12–18%), vegetable (5%, 0–10%) and pasture hay (14%, 8–20%). The cost and benefit analysis showed that the economic benefit of reducing N's environmental impacts offsets the cost of NI application. Applying NI along with N fertilizer could bring additional revenues of $163 ha −1 yr −1 for a maize farm, equivalent to 8.95% increase in revenues. Our findings showed that NI s could create a win‐win scenario that reduces the negative impact of N leaching and greenhouse gas production, while increases the agricultural output. However, NI 's potential negative impacts, such as increase in NH 3 emission and the risk of NI contamination, should be fully considered before large‐scale application.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Use of a whole-cell bioreporter, Acinetobacter baylyi, to estimate the genotoxicity and bioavailability of chromium(VI)-contaminated soils - Bo Jiang; Di Zhu; Yizhi Song; Dayi Zhang; Zengjun Liu; Xu Zhang; Wei E. Huang; Guanghe Li (Biotechnology Letters, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Use of ground-penetrating radar for construction monitoring and evaluation of perpetual pavements - Jiusu Li; Lubinda F. Walubita; Geoffrey S. Simate; Allex E. Alvarez; Wenting Liu (Natural Hazards, 2015)